Pedagogia e as questões ambientais: estudo nas escolas municipais do Ensino Fundamental na cidade de Tocantínia - TO - Bezerra, Liliane Alves (Universidade Federal do Tocantins, 2021)
This research brings as its subject of study: Pedagogy and environmental issues, in the perspective of the pedagogical practices used in the municipal schools of Tocantínia with children aged 7 to 10 years of elementary school. The aim of the study was to learn about the pedagogical practices related to environmental issues in the two schools surveyed. The methodological procedures for conducting the research were bibliographic, documentary, and field research. It is concluded that in the approaches to Environmental Education, it is necessary that universities, the population are involved in this new project of educating, problematizing, and creating critical attitudes in students and social subjects who are together in the teaching and learning process.